Examination of forest growth with GIS and photogrammetry methods on karst areas - Zboray, Zoltán (JOURNAL OF LANDSCAPE ECOLOGY, 2007)
The most common form of land use in Hungarian karsts is forestry. The rate of tree growth in the forest is of utmost importance for forest management, but it is also useful for monitoring purposes. In this study author reviews the possible uses of digital surface models derived from aerial photos in investigating tree growth rates. Two digital surface models were created of a 100 km2 study area in the Bükk Mountains, Hungary by using air photography from the years 1965 and 2004. Tree growth maps were created by extracting the areas’ digital elevation models from these surface models. The results suggest that these digital maps could help for the field measurements in the future.